2018
DOI: 10.1136/bmjspcare-2017-001490
|View full text |Cite
|
Sign up to set email alerts
|

Palliative stenting for oesophagogastric cancer: tumour and host factors and prognosis

Abstract: ObjectivesPalliative self-expandable metallic stent (SEMS) insertion is common in patients not suitable for resection of oesophago-gastric (OG) cancer. Factors which may determine survival however are not clear. The present study examined the relationship between tumour and host factors, including the systemic inflammatory response, and survival of patients undergoing palliative SEMS insertion. MethodsPatients with a diagnosis of OG cancer who were considered suitable for palliative SEMS only without systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Esophageal stent placement is indicated in patients with an expected short-term survival (i. e. less than 3 months) for its rapid relief of symptoms, usually within 1-2 days after stent placement [6]. Several prognostic tools may aid the selection of esophageal stent candidates, but these lack external validation [20][21][22]. The presence of metastases and poor performance status have repeatedly been shown to be associated with poor survival [21][22][23][24].…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal stent placement is indicated in patients with an expected short-term survival (i. e. less than 3 months) for its rapid relief of symptoms, usually within 1-2 days after stent placement [6]. Several prognostic tools may aid the selection of esophageal stent candidates, but these lack external validation [20][21][22]. The presence of metastases and poor performance status have repeatedly been shown to be associated with poor survival [21][22][23][24].…”
Section: Efficacymentioning
confidence: 99%
“…Several prognostic tools may aid the selection of esophageal stent candidates, but these lack external validation [20][21][22]. The presence of metastases and poor performance status have repeatedly been shown to be associated with poor survival [21][22][23][24]. When esophageal stent placement is considered, SEMSs are recommended over self-expandable plastic stents (SEPSs) owing to a lower rate of symptom recurrence and serious adverse events [6].…”
Section: Efficacymentioning
confidence: 99%
“…A research from China also determined its prognostic value in predicting OS and DFS in EJA patients with resection [51]. Park et al suggested that mGPS might be an independent marker for survival in patients with EJA (163 out of 203 participants, including gastric cancer) undergoing palliative self-expandable metallic stent insertion (HR = 1.24, 95% CI: 1.03 -1.49) [52].…”
Section: Biochemical and Coagulation Parametersmentioning
confidence: 99%
“…In recent years, the presence of a preoperative innate systemic inflammatory response (SIR) has also been recognized as a potentially important prognostic marker in EC, in both palliative and curative settings. 10 It is postulated to be related to the upregulation or inappropriate activation of the innate immune response, which suppresses the more useful anticancer adaptive response. 11 It is therefore speculated that the presence of an innate SIR, represented by measurements of the acute-phase reactants C-reactive protein (CRP) and albumin in the form of the modified Glasgow Prognostic Score (mGPS) may be useful to identify EC patients who will have higher rates of postoperative morbidity and poorer prognosis following resection of locally advanced disease.…”
mentioning
confidence: 99%